TH EVALUATION OF THE UNDP’S INTEGRATED COMMUNITY DEVELOPMENT PROGRAMMES IN OYO STATE, NIGERIA Jacob Adejumo AREMU (2014)
The failure of past anti-poverty initiatives during the pre-Structural Adjustment Programme (SAP) and post-Structural Adjustment Programme (SAP) eras in Nigeria motivated the United Nations Development Programme (UNDP), in collaboration with the federal, state and local governments, to jointly take a pragmatic step of initiating the Integrated Community Development Programme (ICDP), a participatory poverty reduction intervention. Literature has shown the extent to which the UNDP/ICDP programme has achieved its objectives successfully in other places but the extent of its implementation in selected communities of Oyo State has not been documented. Therefore, this study evaluated the UNDP’s integrated community development programme in Oyo State, Nigeria. Descriptive survey research design was adopted, using the Context-Input-Process-Product model. The stratified random sampling technique was used to select 2,569 service beneficiaries, 58 service providers, 68 community leaders and 105 government change-agents from 11 out of the 20 ICDP communities. Three instruments were used: ICDP Beneficiary Scale (r=0.93), ICDP Sustainable Human Development Scale (r=0.89) and Service Providers/UNDP/ICDP Assessment Scale (r=0.63). These instruments were complemented with Oyo State and UNDP official documents, 11 sessions of Focus Group Discussion and 22 Key Informant Interviews with service beneficiaries and providers. Three research questions were answered and six hypotheses formulated and tested at P=0.05. Data were analysed using percentages, chi-square and content analysis. The ICDP significantly aided poverty reduction (X2=206.17); over 80.0% of the respondents perceived that the programme greatly contributed to and correlated positively with the 11 indices of sustainable human development promotion. The ICDP significantly influenced the provision of vocational skills enhancement (X2=146.02); and assisted 65.8% of the beneficiaries to acquire more skills and training. It also positively and significantly influenced the provision of social infrastructural amenities (X2=118.01); 111 units of boreholes/deep wells, 7.6km of roads and 11 million naira on medical equipment/services. The programme positively influenced provision of soft loans (X2=89.61); about 45.7% of the beneficiaries were able to obtain 24.8 million naira worth of loan through the ICDP’s micro-credit loan support facilities. The agro-processing equipment support of the ICDP made 73.0% of farmers to enjoy 48 units of agro-equipment; thus enhancing agricultural activities (X2=102.15). About half (49.7%) of the respondents claimed to have enjoyed clean and better sanitation through 98 ICDP samplat latrine projects. The ICDP influenced acquisition of functional literacy (X2=66.42); 4,621 neo-literates were graduated from 24 literacy centres. The programme significantly influenced the general level of citizen participation in the intervention programmes ((X2=187.48). Funding and publicity of the ICDP and the training of project recipients were inadequate, which invariably reduced the impact of the projects. Besides, there was misapplication of seed money for unintended purposes. The United Nations Development Programme’s integrated community intervention in Oyo State contributed positively to the promotion of sustainable human development. There is however the need for adequate publicity, funding and training of recipients, as well as the need to educate beneficiary communities on better application of seed money, to enhance the effectiveness of the UNDP intervention. Keywords: UNDP, Poverty alleviation, Integrated community development programme. Word Count: 487